Internationalising Educational Inspection: Evidence, Transfer and Proposals from Two Erasmus+ Mobilities in Portugal - Fernández López, Maravillas; Rodríguez Romero, Virginia; Jiménez Mesas, Emilia Mª (Avances en Supervisión Educativa, 2026)
This article analyses the professional and organisational value of two experiences of Erasmus+ job-shadowing mobilities carried out in Portugal by three Andalusian education inspectors and contrasts the findings with a national survey of ADIDE members. The study combines direct observation, field notes, documentary analysis, a review of relevant regulations and literature, and descriptive use of survey data. The observed contexts were the external evaluation of a public-school cluster in Oeiras and the visit to Escola Profissional Almirante Reis, a vocational education institution in Lisbon. The results identify six transferable features: rigorous preparation of visits, hypothesis-led interviews, classroom observation focused on pedagogy, a stable inclusion structure through EMAEI, collegial report writing, and a quality culture linked to EQAVET. The survey confirms a positive disposition towards internationalisation while revealing shortcomings in training, professional networks, and institutional support. The article proposes measures to integrate this line of work into inspection planning in Andalusia.